Study of the stability of the electric drive of the oil field mechanism based on the use of mathematical and computer modeling methods - Miraziz V. Sagatov; Volodimir A. Fedorchuk (PROBLEMS OF ENERGY AND SOURCES SAVING, 2026)
Relevance: Electromechanical systems are widely used in mechanical engineering, power engineering, mining, metallurgy, transport, etc. Since significant power consumption is observed during the operation of electromechanical systems, intensive work has been carried out for many years to improve their energy characteristics. Analysis of energy consumption in deep-well pumping of oil in recent years shows an increase in specific energy consumption per 1 ton of extracted oil. This is due to the specific operating conditions of oil equipment. The electric drive of deep-well pumping units, i.e. pumping units, operates under difficult conditions due to periodic changes in the torque on its shaft over a wide range, as well as voltage fluctuations in low-voltage distribution networks. These fluctuations are caused not only by the nature of the load of the electric drives, but also by sharp drops in voltage during self-starting of a group of parallel-operating electric motors or short circuits in the network. Thus, the tasks of designing, constructing, studying modes, testing and debugging electromechanical systems are labor-intensive, and the creation of methods and means for their effective solution using computer modeling is a pressing problem that has not been fully solved, despite significant achievements in this area of research. Aim: analysis and justification of the use of mathematical and computer modeling methods to study the stability of the electric drive of an oil field mechanism. Methods: methods of mathematical and computer modeling and elements of automatic control theory. Results: Using the method of mathematical modeling with the use of computer modeling software, the problem of studying the stability of the electric drive was considered, which allowed us to draw a conclusion about the use of contactless synchronous electric motors with external magnetic circuits and a rotor with claw poles in oil production electrical equipment.